Elucidating the Immune-Related Mechanisms by Which Probiotic Strain Lactobacillus casei BL23 Displays Anti-tumoral Properties - Jacouton, Elsa; Michel, Marie-Laure; Torres-Maravilla, Edgar; Chain, Florian; Langella, Philippe; Bermúdez-Humarán, Luis G. (Frontiers in Microbiology, 2019)
We have recently described antitumor properties of Lactobacillus casei BL23 strain in both a mouse allograft model of human papilloma virus (HPV)-induced cancer and dimethylhydrazine-associated colorectal cancer. However, the mechanisms underlying these beneficial effects are still unknown. Interestingly, in vitro cellular models show that this bacterium is able to stimulate the production of high levels of IL-2. Because this cytokine has well-known antitumor properties, we decided to explore its role in the anti-cancer effects of BL23 using the HPV-induced cancer model. We found a negative correlation between IL-2 and tumor size confirming the necessity of IL-2 to protect from tumor development. Then, we blocked IL-2 synthesis using neutralizing monoclonal antibodies in mice that were challenged with lethal levels of tumor cells; this led to a significant reduction in the protective abilities of BL23. Next, we used a genetically modified strain of Lactococcus lactis to deliver exogenous IL-2 to the system, and in doing so, we were able to partially mimic the antitumor properties of BL23. Additionally, we showed the systemic role of T-cells in tumor protection through a negative correlation between tumor size and T-cells subpopulations and an increasement of BL23-specific local Foxp3 levels in tumor-bearing mice. Finally, we observed a negative correlation between tumor size and NK+ cells, but local recruitment of NK cells and cytotoxic activity appeared specific to BL23 treatment. Taken together, our data suggest that IL-2 signaling pathway plays an important role in the anti-tumoral effects of probiotic strain L. casei BL23. These results encourage further investigation in the use of probiotic strains for potential therapeutic applications to clinical practice, in particular for the treatment of colorectal cancer. Furthermore, our approach could be extended and applied to other potential beneficial microorganisms, such as gut microbiota, in order to better understand the crosstalk between microbes and the host.